Hybrid nanosystems based on natural polymers as protein carriers for respiratory delivery: stability and toxicological evaluation - Rodrigues, Susana (2015)
Chitosan/carrageenan/tripolyphosphate nanoparticles were previously presented as holding potential for an application in transmucosal delivery of macromolecules, with tripolyphosphate demonstrating to contribute for both size reduction and stabilisation of the nanoparticles. This work was aimed at evaluating the capacity of the nanoparticles as protein carriers for pulmonary and nasal transmucosal delivery, further assessing their biocompatibility pattern regarding that application. Nanoparticles demonstrated stability in presence of lysozyme, while freeze-drying was shown to preserve their characteristics when glucose or sucrose were used as cryoprotectants. Bovine serum albumin was associated to the nanoparticles, which were successfully microencapsulated by spray-drying to meet the aerodynamic requirements inherent to pulmonary delivery. Finally, a satisfactory biocompatibility profile was demonstrated upon exposure of two respiratory cell lines (Calu-3 and A549 cells) to the carriers. A negligible effect on cell viability along with no alterations on transepithelial electrical resistance and no induction of inflammatory response were observed. (C) 2015 Elsevier Ltd. All rights reserved.